Comparison of The Effectiveness Antibacterial Test of Natural Ingredients and Antibiotic in Salmonella typhi Isolated from Hospital Waste and Household Waste - Syamsul Bahri; Rizal Umami; Ferniawan Ferniawan; Moammar Qadafi; Sekar Partiwi (Jurnal Penelitian Pendidikan IPA, 2023)
Salmonella typhi is a bacterium that causes salmonellosis which is a serious disease in Indonesia and is still endemic. Until now, the treatment and handling of cases of bacterial infection are still using antibiotics. The comparison of antibacterial effectiveness using turmeric extract, a ginger extract which is a natural ingredient with the antibiotics Ampicillin and Ciprofloxacin on Salmonella typhi isolates from hospital waste and household waste has been conducted. The purpose of this research is to compare the antibacterial effectiveness of Curcuma longa (turmeric) extract, Zingiber officinale (Ginger) extract, Ampicillin, and Ciprofloxacin antibiotics in inhibiting the growth of Salmonella typhi which are isolated from hospital waste and those isolated from household waste. This research is experimental research (experimental), using a control group and the research is carried out in a laboratory. The data collection technique was carried out by measuring the inhibition zone. Size of the inhibition zone of hospital isolates after treated by turmeric and ginger extract is smaller than household isolates. This result indicates that excessive usage of antibiotics will be able to increase the resistance or immunity of Salmonella typhi. Substances which are contained in turmeric and ginger extracts have ability to inhibit the growth of Salmonella typhi, with strong category against hospital isolates and very strong category against household isolates. It is concluded that turmeric and ginger extracts are able to    substitute synthetic antibiotics such as Ampicillin.